The Impact and Clinical Prediction of Hyperglycemia During Parenteral Nutrition for Nondiabetic Patients After Gastrectomy for Gastric Cancer - Lan, Ning; Chen, Xiaohua; Lu, Ying; Zhou, Yujie; Kong, Fei; Zhao, Yining; Jiao, Fuzhi; Zhang, Lin; Yuan, Wenzhen (Frontiers in Nutrition, 2022)
Background and Purpose: Hyperglycemia (HG) is associated with increased postoperative complications. This study aims to evaluate the effect of HG during supplemental parenteral nutrition (SPN) on short-term prognosis in nondiabetic patients undergoing gastrectomy for cancer and to analyse the risk factors and prevention methods for HG. Methods: A total of 359 patients were divided into three groups according to capillary blood glucose (CBG) during SPN: normoglycemic patients (≤125 mg/dL), mild HG (125 200 mg/dL), and severe HG (>200 mg/dL). The effect of CBG on postoperative short-term outcomes was analysed. Multivariate regression was performed to investigate influencing factors for severe HG. The safety and efficacy of insulin addition to total nutrient admixture (TNA) for the prevention and management of hyperglycemia were assessed by propensity score matching (PSM). In addition, regression analysis was performed in the noninsulin group to investigate the predictive factors of severe HG, and a nomogram was plotted. Results: The postoperative complication rate was 18.9%, but it was significantly higher in patients with severe HG than in mild HG and normoglycemic patients (25.2, 15.0, and 10.0%, p<0.05). Multivariate logistic regression analysis showed that anaemia, myosteatosis, higher postoperative CBG before TNA infusion, and insulin in the TNA were independent influencing factors for severe HG. Based on the above factors, 75 pairs of patients (insulin group and noninsulin group) with comparable baseline data were successfully matched by PSM. The HG incidence and the glycemic fluctuation were significantly improved through 1 U insulin/6 g glucose (1/6 scheme) to TNA. A nomogram containing hemoglobin, skeletal muscle radiodensity, pre-SPN CBG, and pTNM stage with good predictive efficacy (C-index: 0.750) was constructed based on the noninsulin group. Conclusion: Poor postoperative glycemic control was related to worse outcomes in nondiabetic patients undergoing gastrectomy. Preoperative anaemia, myosteatosis, and high postoperative CBG before TNA infusion are risk factors for severe HG. Insulin in TNA can improve the blood glucose control of patients. Our proposed nomogram rendered an individualized predictive tool for HG during SPN, which helps screen high-risk patients requiring insulin therapy. Future studies with larger samples are needed to develop a complete insulin application protocol for SPN.